CROSS-LANGUAGE PRACTICES AND SPEAKING TECHNOLOGY IN HIGHER EDUCATION FOR STRENGTHENING ENGLISH COMMUNICATION COMPETENCE - Ervina CM Simatupang; Heri Heryono; Lilies Youlia Friatin; Bambang Ruby Sugiarto (University of Kuningan, 2025)
Accomplishment in higher education recently depends on the ability to communicate effectively in English; due to increasingly globalized academic setting. This essay investigates the creative ways that speaking technology and cross-language exercises might be combined to improve students' proficiency in English communication. By utilizing students' current linguistic resources, cross-language practices, which entail the purposeful use of different languages, can promote deeper comprehension and retention of English language abilities. When combined with cutting-edge speaking technology, such AI-driven language learning tools and speech recognition software, these approaches provide a dynamic and engaging means of honing English communication skills. With a focus on practical application in academic and professional contexts, the study investigates the effects of these combined techniques on students' language proficiency. This research is a comparable passage that has been adjusted for the study's setting. The study involved 45 students from different academic disciplines, 60% of whom were female and 40% of whom were male, and used a sequential explanatory mixed-method approach to investigate their views and experiences about cross-language practices in combination with speaking technology. Surveys, pre- and post-speaking evaluations for descriptive analysis, and reflective notebooks for qualitative insights were all used in the data collection process. The study of descriptive data was done using theme analysis. As evidenced by the overwhelmingly favorable response from participants, the data showed that integrating student languages alongside English, backed by speaking technology, dramatically increased their English communication skills.